Gene Action, Heterosis and Combining Ability in Maize Hybrids A- Using Half Diallel Analysis - Mohammed Ali Hussain; Khalid Mohamad Dawod; Abbas Alo Khether (Kufa Journal for Agricultural Sciences)
A diallel cross comprising of eight pure lines of maize, ZP-505, IK58, HS, DK-17, ZP-430, ZP-595, U,N44052, and POL-158, was studied for nine traits (number of days to silking, number of days to tasseling, plant height, ear height, leaf area, number of rows per ear, number of grains per300-grain grain weight, and grain yield per plant, to identify the combining ability effects, nature of gene action heterosis. The results revealed that the mean square for all genotypes was highly significant for all which’s that is an indication of the genetic diversity between parentcausesch cause significant differences between single crosses among them. Also, it was shown that the mean square due to general and specific combining abilities was highly significant for all traits indicated the presence of additive and dominant gene effects controlling the effect of all traits. The ratio of general combining ability components to the specific combining ability components was less than one for all traits indicated that the dominance gene effects were more prominent for all studied traits. The line ZP-595 and POL-158 were the best general combiners for larger number of traits including grain yield per plant, and the crosses (ZP-505 x UN44052) and (HS x DK-17) showing highly significant specific combining ability effects and heterosis for larger number of traits and could be utilized for developing high yielding hybrid varieties as well as for exploiting hybrid vigor. The narrow sense heritability was low for all traits and ranged from 3.23% for 300 grain weight and 23.13% for number of days to silking.